Striving For Superiority Of Margaret Tate In Anne Fletcher's The Proposal Movie (2009): An Individual Psychological Approach - DARNAWI., SETYO (2012)
The problem of this study is to reveal how striving for superiority on the major character. The objective of the study is to analyze the movie based on the major character in The Proposalmovies based on Individual Psychological Analysis. The study is a literary study, which can be categorized into a qualitative study. The object of this study is The Proposalmovie. The data sources are primary and secondary data sources. The primary data source is the movie script and the secondary data are related to the primary data that support the analysis such as some books of psychology and website related to the research. The method used for collecting data is library research and documentation. The technique of data analysis is descriptive analysis. Based on the analysis, the writer concludes that the problem faced by the major character is struggle to go out of her condition, it causes the writer to use individual psychological perspective such as: Inferiority Feeling, Striving for Superiority, Fictional Finalism, Style of Life, Social Interest, and Creative Power. By using this method, it is known how Margaret Tate as the major character can solve her problem.